Rational Prescribing of Oral Dosage Forms of Medicines to Children at a Teaching Hospital in Sri Lanka - Nadeshkumar, A.; Sathiadas, M.G.; Sri Ranganathan, S. (The Pharmaceutical Journal of Sri Lanka, 2020)
Purpose: Rational use of medicine includes prescribing practices at all levels. According to the available literature prescribing practices especially in children has been a challenge and poor prescribing practices are seen widely. Hence there is a need to investigate whether oral dosage forms of medicines are prescribed rationally to children. The objective of this study was to describe the rational prescribing practice of oral dosage forms of medicines to children in a teaching hospital in Sri Lanka. Methods: A descriptive cross-sectional study was conducted to assess the prescribing practices of 1800 oral dosage forms of medicines prescribed to children under the age of 12 years over a period of one year using validated indicators. Required data were extracted from the prescriptions using a structured pre-tested data extraction sheet. Descriptive statistics was used to analyse the data. Results: A total of 2195 medicine were prescribed during the study period and 1800 (82%) were oral dosage forms. Only 24 % of the oral dosage forms were prescribed appropriate to the weight of the child. The majority of the oral dosage forms were liquid and solid dosage forms were prescribed even to children under two years. Capsules were rarely prescribed to children. Conclusion: Prescribing practices of oral dosage forms of medicines to children has to be improved in the healthcare setting.
Keywords: Rational use; Oral dosage form; Prescribing; Children; Indicators